Evidence for the Brief Mysticism Scale: Psychometric Properties, and Moderation and Mediation Effects in Predicting Spiritual Self-Identification. Issue 3 (3rd July 2021) - Streib, Heinz; Chen, Zhuo Job
ABSTRACT: How are mystical experiences related to self-rated spirituality? Is the recently developed short 8-item version of Hood's Mysticism Scale an efficient measurement? The current study expands evidence for both questions using N = 1, 582 American and N = 1, 492 German samples measured in three waves, average 4 to 5 years apart. Results show that the 8-item brief M-Scale has good psychometric property evidenced by 1) measurement invariance across time, and 2) good test–retest reliability. Results further demonstrate that the 8-item brief M-Scale 3) moderates the effect of self-rated religiosity on self-rated spirituality, and 4) mediates the prediction of self-rated religiosity on self-rated spirituality over time. We conclude that the M-Scale can be used as a measure for self-attributed spirituality and that the 8-item brief version of the M-Scale can be used when questionnaire length is an issue.